Optimization of Community Service and Community Services in Reducing the Number of Accidents in the Legal Area of ​​the Bandung Police - W., Bastian Dhira Octavianto (Police Studies Review, 2024)
There are four factors that cause traffic accidents: human factors, vehicle factors, road factors, and weather factors. Human factors are the main cause of traffic accidents due to the condition of the driver, making it the primary reason for accidents. Therefore, efforts are needed to prevent traffic accidents in order to reduce the accident rate. For this reason, the author is interested in conducting research and writing a thesis with the problem statement: “What is the role of Dikmas Lantas in reducing traffic accidents in the jurisdiction of Polrestabes Bandung?” The research literature referred to is the study by Meivito Bayu W (2014). From Meivito’s thesis, the similarity in the research is about traffic, while the difference in this thesis is that the author focuses on the role of Dikmas Lantas activities in reducing traffic accidents in the jurisdiction of Polrestabes Bandung. The theories and concepts that form the basis of this research include George R. Terry’s Management Theory, Eerett M. Roger’s Communication Theory, and the concepts of Policing Science and Dikmas Lantas found in the Vademikum Lantas (2009). Based on the research findings and discussion, the conclusion is that the Dikmas Lantas Program of Polrestabes Bandung has made various efforts to minimize these issues, such as preventing traffic violations and accidents, as well as striving to raise legal awareness among motor vehicle drivers through outreach activities, leading ceremonies, routine operations, and more. The factors that may hinder the optimization of the Dikmas Lantas Program include human factors, budget, methods, and targets. Meanwhile, the supporting factors include the availability of facilities and infrastructure that can attract the public of Bandung to learn about traffic issues, such as the availability of traffic parks, the Polantas Village, accident monuments, and good cooperation with stakeholders. The recommendations include increasing the number of Dikmas Lantas Unit personnel, ensuring that Dikmas Lantas Unit members have a bachelor’s degree, and that they have attended (Dik Bangspes Dikmas Lantas) to ensure more professional Dikmas Lantas outreach activities. It is also suggested that a special budget for the Dikmas Lantas Unit be proposed to the Police Chief through the DIPA of the National Police according to their needs.